Analysis of Teacher Needs for Science E-Book Teaching Materials Using the PBL Model with an In-Depth Learning Approach in Junior High Schools - Kusmawati Kusmawati; Insih Wilujeng; Susilowati Susilowati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to analyze Science teachers’ needs regarding the development of a digital learning resource in the form of an e-book based on the Problem-Based Learning (PBL) model to support deep learning in junior high schools. Using a descriptive qualitative design, data were collected from 30 Science teachers in Meranti Islands Regency through an online questionnaire and interviews. The findings reveal that Science learning is still dominated by conventional printed textbooks, resulting in limited student engagement and challenges in understanding abstract concepts. Teachers identified several barriers to the use of digital learning materials, including limited ICT competence, insufficient technological facilities, and time constraints. Despite these challenges, the study indicates a strong demand for e-books with multimedia features, interactive components, structured project guidance, and collaborative learning support. Teachers believe that a PBL-based e-book has the potential to improve students’ concept mastery, critical thinking, and problem-solving skills by enabling self-paced learning and providing opportunities for inquiry and collaboration. These results underscore the importance of developing a PBL-oriented Science e-book as an innovative solution to align instructional practices with the Merdeka Curriculum and digital learning transformation